A versatile drug delivery system targeting senescent cells - Daniel Muñoz‐Espín; Miguel Rovira; Irene Galiana; Cristina Giménez; Beatriz Lozano‐Torres; Marta Paez‐Ribes; Susana Llanos; Selim Chaib; Maribel Muñoz‐Martín; Alvaro C Ucero; Guillermo Garaulet; Francisca Mulero; et al. (EMBO Molecular Medicine)
Abstract Senescent cells accumulate in multiple aging‐associated diseases, and eliminating these cells has recently emerged as a promising therapeutic approach. Here, we take advantage of the high lysosomal β‐galactosidase activity of senescent cells to design a drug delivery system based on the encapsulation of drugs with galacto‐oligosaccharides. We show that gal‐encapsulated fluorophores are preferentially released within senescent cells in mice. In a model of chemotherapy‐induced senescence, gal‐encapsulated cytotoxic drugs target senescent tumor cells and improve tumor xenograft regression in combination with palbociclib. Moreover, in a model of pulmonary fibrosis in mice, gal‐encapsulated cytotoxics target senescent cells, reducing collagen deposition and restoring pulmonary function. Finally, gal‐encapsulation reduces the toxic side effects of the cytotoxic drugs. Drug delivery into senescent cells opens new diagnostic and therapeutic applications for senescence‐associated disorders.